Expanding the Collection of GlcNAc Analogues for Bacterial Sialic Acid Uptake Inhibition - Tranell,Måns (2025)
Antibiotic resistance is a threat that could result in severe consequences for the public health. The synthesis of new antibiotics is therefore increasingly more important. Sialic acid is a sugar which aids bacterial growth, but the opposite effect could occur if bacteria were prevented from utilizing this sugar. This could be achieved through inhibition of pmSiaT, a protein which transports sialic acid into bacteria. The aim of this study is to design and synthesise a molecule with high pmSiaT binding affinity, to physically block the transport channel. GlcNAc was chosen as a starting point. This molecule is similar to sialic acid, but chemical modifications can be performed more easily due to the absence of the glycerol side chain. Three GlcNAc positions were modified on each drug candidate. NanoDSF protein tests were performed which showed that all drug candidates bound to pmSiaT at varying degrees.
Keywords: Organic chemistry; GlcNAc; pmSiaT